Evaluation of the Antimicrobial Activity of Propolis Ointment Against Staphylococcus aureus (Nigerian Journal of Pharmaceutical Research, 2023)
Background: This study was carried out to determine the antimicrobial effect of propolis ointment formulations against Staphylococcus aureus.  Methods: Propolis was extracted with 70 ml Ethanol (99 %) and the ointment was prepared by incorporating the extract into emulsifying ointment BP. Formulations were evaluated against Staphylococcus aureussing agar diffusion test. Physicochemical properties of the formulation (pH, viscosity and spreadability) were determined using a pH meter, and viscometer. Homogeneity and texture were also determined. Differences in means were evaluated by the independent student t-test at p-value < 0.05.Results: The ointment was dark brown, greasy with a smooth texture. The viscosity of the propolis emulsifying ointment and simple ointment was 11133 ± 1229 and 11800 ± 1100 cP with spreadability of 6.32 ± 1.33 and 6.00 ± 2.40 mm2/g respectively. The pH of the simple and emulsifying ointment was 7.10 ± 0.05 and 7.22 ± 0.06 respectively. There was however reduced pH, spreadability and viscosity of the formulation over a period of 90 days (3 months) resulting in more acidic preparations less than 6 (5.65) in batch F2. Depth of penetration of the simple ointment was between 6.00 ± 0.8 mm to 7.55 ± 0.8 mm and 6.75 ± 0.5 mm to 9.20 ± 1.10 mm for the emulsifying ointment over a period of 14 days. The minimum inhibitory concentration of the propolis extract against Staphylococcus aureus was 300 mg/ml. Inhibition zone diameter of the simple and emulsifying ointment were 16.5 ± 1.3 mm and 17.0 ± 1.2 mm respectively.Conclusion: Propolis can be formulated as an ointment for the treatment of bacterial skin infections. The physicochemical properties of the formulation were stable with gradual decline over a period of 3 months. The propolis ointment exhibited antimicrobial activity against Staphylococcus aureus.